Consumer Awareness on Food Poisoning - Sahingoz, Semra Akar; Sahin, Hande (Pakistan Journal of Nutrition, 2009)
This study aims to determine the level of knowledge of consumers on types of food poisoning and whether or not they have had food poisoning in the past. The research sample consisted of 232 people. The research data were collected using a questionnaire, face-to-face interviews and observation. The data were analyzed using SPSS 13.0 for Windows. Chi-square test was applied in order to determine whether a statistical difference between the participants existed or not, by taking their education levels as the variable and the results were tabulated using p = 0.005 and p = 0.01 significance values as principle. It was determined that 46.6% of the participants had experienced a problem because of food and 29.5% of these were nausea problems, 28.7% of them got poisoned because of the food consumed in their cafeteria at work and 29.6% was because of chicken, 85.2% of the consumers were poisoned in the summer, 33.3% were poisoned in 2007, 81.5% had not gone to a health center, of those who had gone to a health center 75.0% were identified as poisoned. As the education level of the consumers increase, they start to have some knowledge on HACCP but this knowledge is incomplete (p<0.01).